Between Politics and Finance: Hong Kong's "Infinity War"? - Alessia Amighini (Pubblicazioni ISPI, 2020)
As the Covid-19 pandemic strikes hard, protests in Hong Kong appear to have abated. Distant seem the days when yellow umbrellas and balaclavas saturated global media. And yet, just like at the start of what has now come to be known as the 2019 "global protest wave", Hong Kong remains at the frontline of political contestation worldwide. The protests against the 2019 Hong Kong anti-extradition law unearthed one of the main points of contention between Hong Kong and mainland China. Through the protests, China's increasingly assertive stance has found a counterweight, revealing how important the city is to Beijing. China's actions towards Hong Kong might serve as a litmus test for Beijing's ability to mediate and pacify its neighbourhood. Meanwhile, the Covid-19 pandemic risks further heightening tensions between the Hong Kong and the mainland. What makes Hong Kong so special? To what extent have the protests exacerbated or eased over time? How will the city's role in mainland China's outward-looking plans change, if the protests continue?